Penilaian E-Audit Readiness dengan Pendekatan Framework STOPE pada Badan Pemeriksa Keuangan (BPK) RI Perwakilan Provinsi Banten - Abdul Latif; Wing Wahyu Winarno; Surjono (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
E-audit is an integral part of the Implementation of e-government in the audit board of Republic of Indenesia (BPK RI). Implementation of e-audit carried out in stages based on the grand design and road map starting from 2010 to 2014. Its success parameter largely determined by the extent of BPK RI readiness, organization and human resources towards the implementation of e-audit.The aims of this study were to measure the readiness of BPK RI Banten Province Representative to the implementation of e-audit. E-audit readiness assessment in this study using STOPE Framework by evaluating the 5 domains, 14 sub-domain (issues), and 60 sub-sub-domains (factors).The results of data analysis showed that the BPK RI Banten Province representative is on ranked 3 (ready) to implement the e-audit. On four domains (Strategy, Technology, People, and Environment), BPK RI Banten Province Representative is ranked 3 (ready) to implement the e-audit. Nonetheless, in term of Domain Organization, BPK RI Banten Province Representative is ranked 2nd (almost ready) to implement the e-audit.